Resources quantity and nurse welfare in the quality of nursing services - Sari, Rian Maylina; Buhari, Basok; Octavia, Dian (Riset Informasi Kesehatan, 2023)
Background: Nursing management is a group of nurse managers who manage nurses’ organization and efforts, which eventually becomes a nursing process. Nurse resource development needs to be done to maintain the quality of nursing in providing nursing care to patients. One of the reasons for the low ability of quality of nursing services is the low level of well-being. The care received is not by rights, so it can affect a person’s performance, disrupting the quality of nursing services. This study aims to determine the number of resources and the level of welfare of nurses in the quality of nursing services. Methods: this research is a quantitative study with a cross-sectional data analysis method using the Chi-Square statistical test within the 5% significance limit, the total sampling technique with a sample size of 81 nurses. The data was collected with a questionnaire regarding the resources and welfare of nurses in the quality of nursing services. Result: statistical test results obtained v-value 0.007 <0.05 indicating a relationship between human resources and the quality of nursing services, 0.014 <0.05, which indicates a relationship between the welfare of nurses and the quality of nursing services. The findings related to the relationship between the number of nursing human resources and the quality of nursing services show that 55.8% of the quality of service is not good because the number of human resources is not good or does not meet needs, while the welfare of nurses on the quality of nursing services is 56.8% which is not good. Conclusion: the resources and well-being of nurses have a relationship with the quality of nursing services. Adequate resources and well-being can improve the quality of nursing services